The Influence of Price, Promotion and Location on Purchasing Decisions For Subsidized Houses at PT. ABGI PUTRA PERKASA - Ayunia Ayunia; Tika Nirmala Sari (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
The purpose of this study was to determine and analyze the effect of Price on Purchasing Decisions. To determine and analyze Promotion on Purchasing Decisions. To determine and analyze the Location on Purchasing Decisions. To determine and analyze the effect of Price, Promotion and Location on Purchasing Decisions for Subsidized KPR Houses at PT ABGI PUTRA PERKASA. In this study, an associative approach was used to determine the relationship between each variable. The data presented in the form of quantitative data, namely testing and analyzing data with numerical calculations and then drawing conclusions and testing. In this study, the object studied was a Subsidized KPR House at PT ABGI PUTRA PERKASA with an unknown population and a sample of 61 people with a sample draw using the Lemeshow formula.The results of this study are Price has a significant effect on Purchasing Decisions. Promotion has a significant effect on Purchasing Decisions. Location has a significant effect on Purchasing Decisions. And Price, Promotion and Location have a significant effect on Purchasing Decisions for Subsidized KPR Houses at PT ABGI PUTRA PERKASA.